The impact of pre-school on adolescents' outcomes: Evidence from a recent English cohort - Patricia Apps; Silvia Mendolia; Ian Walker (Institute for the Study of Labor (IZA), 2012)
This paper investigates the relationship between attendance at nursery school and children's outcomes in adolescence. In particular, we are interested in child cognitive development at ages 11, 14 and 16, intentions towards tertiary education, economic activity in early adulthood, and in a group of non-cognitive outcomes, such as risky health behaviours (smoking, early pregnancy, use of cannabis) and personality traits (feelings and commitments about school; psychological well-being). Using matching methods to control for a very rich set of child's and family's characteristics, we find that pre-school childcare largely improves results in cognitive tests at age 11 and 14 and 16, and has a positive effect on intentions towards further education and economic activity at age 19-20. Positive effects are especially noticeable for children coming from disadvantaged socio-economic backgrounds. Results on non-cognitive outcomes are more mixed: we do not find any evidence of improvement in psychological well-being, but we do find some positive effects on health behaviours.
Keywords: J13; I21; 330; childcare; child outcomes; Frühkindliche Bildung; Kognition; Gesundheitsvorsorge; Persönlichkeitspsychologie; Erwachsene; Großbritannien